Corrective Osteotomy in a Dog to Address Increased Distal Femoral Procurvatum Ascribed to a Distal Femoral Salter-Harris Type V Injury - Memarian, Parastoo; Lewis, Daniel D.; Bucci, Massimo; Isola, Maurizio (VCOT Open, 2023)
Increased distal femoral procurvatum has been reported sporadically in dogs following malunion of Salter-Harris type I, II, and III fractures of distal femur. The resultant increased procurvatum can be poorly tolerated because of subsequent loss of stifle extension. This case report represents a dog with the increased procurvatum of the distal femur ascribed to a previous Salter-Harris type V injury. Surgical planning and successful outcome following the corrective procedures have been documented. A 6.5-month-old fox-terrier presented with a persistent weight bearing left pelvic limb lameness, 2 months after being hit by a car. The predominant orthopaedic finding was a 20-degree decrease in left stifle extension. Radiographic and computerized tomography evaluation revealed premature eccentric closure of the left distal femoral physis ascribed to a previous Salter-Harris type V injury. The left femoral procurvatum was 30 degrees. The left tibial plateau angle was increased by 11.5 degrees compared with the right. The femoral deformity was characterized, and a corrective procedure was planned using Paley's centre of rotation of angulation methodology. A cranial closing wedge ostectomy of the left distal femur was performed and stabilized using a locking plate. Proximal tibial epiphysiodesis was also performed to reduce the tibial plateau slope. Union of the osteotomy site and reduction in tibial plateau angle by 5.4 degrees were documented 50 days after surgery with a good functional outcome.
Keywords: dog; femur; corrective osteotomy; increased procurvatum; Salter-Harris type V